Geometry texts: a different look for our times - Rocha Fontalvo, Yolima; Tovar Ortega, Teremy; Tovar Ortega, Teremy; Tovar Ortega, Teremy (Corporación Universitaria Americana, 2021)
Introduction: The function of textbooks as a didactic resource and the impact they have on mathematics education, particularly geometry, makes it pertinent to carry out hermeneutic and critical analyzes of the characteristics and adaptations to reality. current Colombian. Objective: This research seeks to study mathematics school textbooks, in which we find the subject of geometry immersed, through the observation of the structure they use, in such a way as to verify if they contribute to the generation of significant learning. in the student body, and not simply become a continuation of classes. Method and/or methodology: A content analysis design was used as a technique for the objective, systematic and qualitative description of the manifest content of the communications, in order to interpret it. The most relevant results show the need for school textbooks to point to digital texts where the resolution of the deficiencies presented in current texts is focused. Conclusion: through the digitization of geometry texts, it is possible to contribute to the improvement of visualization through interactive and dynamic environments of more assertive content in the area.